Pattern of loco‐regional relapses and treatment in pediatric esthesioneuroblastoma: The French very rare tumors group (Fracture) contribution. Issue 4 (13th January 2020) - Dumont, Benoît; Fresneau, Brice; Claude, Line; Defachelles, Anne‐Sophie; Couloigner, Vincent; Puget, Stéphanie; Brisse, Hervé J; Fréneaux, Paul; Lacour, Brigitte; Orbach, Daniel
Abstract: Background: Esthesioneuroblastoma (ENB) is a rare neuroectodermal tumor that seldom occurs during childhood. Multimodal treatments are currently proposed, but the place of each therapy is still in debate. Our objective is to describe clinical evolution, especially the pattern of relapses and determine contributors to tumor progression. Procedure: Medical charts of all children (≤18 years) affected by ENB treated in France from January 1990 to December 2015 were retrospectively analyzed. Results: Eighteen patients were selected (10 males). Median age at diagnosis was 12.2 years (0.9‐18). Tumor extension was Kadish stage A (n = 1), B (n = 3), C (n = 10), and D (n = 4). Hyams histological grades were I (n = 1), II (n = 3), III (n = 6), and IV (n = 6) (in two cases not defined). Initial cervical nodal spread was assessed by magnetic resonance imaging (n = 15), computed tomography scan (n = 16), fluorodeoxyglucose‐positron emission tomography‐computed tomography (n = 7), and cytological/histological analysis (n = 2). N1 stage was confirmed by imaging in two of 18 cases and one of two cases had cervical node dissection with neck irradiation (58 Gy). After a median follow‐up of survivors of 7.6 years (3.8‐17.9), 10 patients developed neuromeningeal progression, whereas no cervical nodal relapse occurred and only eight survived. Both 5‐year overall and event‐free survival rates were 44.4% (±11.7%). Conclusions: The poor prognosis is mainly related to neuromeningeal dissemination that should be considered during treatment strategy. However, cervical lymph node relapse is rare.